SYMBOLIC SPACE CONSUMPTION AND THE SOCIALITY IN THE NEW PUBLIC SPHERES: THE CASE OF FATIH HORSE BAZAAR - Bayram SEVİNÇ (Fırat University, 2019)
Coffee-houses and cafes have been the main places of publicity and sociality from the Ottomans up to date. Coffee-houses that emerged as a secular space in Ottoman social structure have been loaded many functions and been an essential area of sociality over time. In the Republic, this area has continued on the one hand and undergone many transformations on the other. The most fundamental transformation has been emerged in regarding to coverage different social preferences and being re-designed according to modernization. Thus, these areas that shaped by societal have also been an inspection area both for society and the state at the same time. It is aimed to move away from the oriental mentality by modernization of coffeehouses in the early stages of the Republic by the effect of the modernization paradigm. Thus the modern subject tended to the new coffee-houses (that having a collection of newspapers and magazines for its customers) and later to cafes. The new Muslim subject has seen the cafes as an intellectual choice in recent years. It is considered that the cafes are places that the identity and construction of discourse are distinctive and the female gender patterns are made visible through them. New Muslim subject’s rhetorical and practical join to the mixed places is facilitated through the cafes. The cafes as new places of the modern society’s sociality are taken as a problematic in this study for the new Muslim subject. In this context, primarily coffee houses and cafes are compared by a functional analysis using a historical comparative perspective. Subsequently, thematic spaces that arise after the conversion of Fatih Horse Bazaar by being decorated with cafes and restaurants as a street were analyzed by the technique of participant observation. Thereby, the human-city relationship is discussed in terms of the qualities of the new spaces and their frequent customers.